Debug and test of microcontroller-based applications using the boundary scan test infrastructure - Gustavo R. Alves (1997)
Microcontroller based applications are usually debugged with the assistance of In-circuit emulators and logic analysers. However, these traditional debug tools represent a huge investment for use in classes with several groups of students working at the same time. The development of a new low-cost debug tool that uses the Boundary Scan Test infrastructure to implement the basic functionality provided by an In-circuit emulator and a logic analyser is a possible solution to overcome this economical problem. To reduce costs the Boundary Scan Test infrastructure is controlled through the parallel port of a normal Personal Computer, now widely available in classrooms.